2017
DOI: 10.1017/s0030605317000199
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of primate hunting in riverine communities in Central Amazonia

Abstract: In many regions primates are an important dietary resource for isolated human populations, and they are among the most hunted species by traditional and indigenous communities in the Neotropics. Little is known about the characteristics or the spatial and temporal patterns of hunting, which limits a more detailed evaluation of its impact. We describe, quantify and analyse the spatial dynamics of primate hunting in the várzea (seasonally flooded forest) and paleovárzea (characterized by a series of low-lying ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…The results indicate a greater slaughter of species without a hunting ban. However, this result may be masked by other factors, such as abundance and spatial distribution of prey and the dynamics of hunting territories (Collinge 2001, Constantino 2015, Pereira et al 2017, as later evidenced by the justifications for not hunting certain species. These factors will also influence the rate of slaughter.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate a greater slaughter of species without a hunting ban. However, this result may be masked by other factors, such as abundance and spatial distribution of prey and the dynamics of hunting territories (Collinge 2001, Constantino 2015, Pereira et al 2017, as later evidenced by the justifications for not hunting certain species. These factors will also influence the rate of slaughter.…”
Section: Discussionmentioning
confidence: 99%
“…Into the One Health context, T. gondii infection in primates poses a direct risk to human health, especially for traditional populations in Amazonia, for which primates can be important source of protein 26 . Furthermore, infected primates can indirectly help to spread the pathogen by infecting their natural predators, the big cats, which are the parasite's definitive hosts and play an essential role in the maintenance and stability of ecosystems 27 .…”
Section: Resultsmentioning
confidence: 99%
“…a direct risk to human health, especially for traditional populations in Amazonia, for which primates can be important source of protein. 26 Furthermore, infected primates can indirectly help to spread the pathogen by infecting their natural predators, the big cats, which are the parasite's definitive hosts and play an essential role in the maintenance and stability of ecosystems. 27 This study found no evidence that primate populations in the region have had contact with the parasite, although the low sampling of individuals per species (1-4 individuals) may have resulted in inaccurate estimates of T. gondii prevalence in these populations.…”
Section: Into the One Health Context T Gondii Infection In Primates P...mentioning
confidence: 99%
“…Wild meat is other important protein source for rural Amazonian populations; however, uncontrolled hunting may lead to a decrease in populations of some species—such as the paca Cuniculus paca [ 18 ]. Thus, it is necessary to quantify the target fauna [ 19 ] and establish the management of the main hunted species [ 20 ]. The regulation and management of subsistence hunting are imperative to ensure food security to the forest inhabitants and the wildlife resources on which they depend.…”
Section: Resultsmentioning
confidence: 99%